2021
DOI: 10.1093/molbev/msab364
|View full text |Cite
|
Sign up to set email alerts
|

Phylogeography Reveals Association between Swine Trade and the Spread of Porcine Epidemic Diarrhea Virus in China and across the World

Abstract: The ongoing SARS-CoV-2 pandemic has exposed major gaps in our knowledge on the origin, ecology, evolution, and spread of animal coronaviruses. Porcine epidemic diarrhea virus (PEDV) is a member of the genus Alphacoronavirus in the family Coronaviridae that may have originated from bats and leads to significant hazards and widespread epidemics in the swine population. The role of local and global trade of live swine and swine-related products in disseminating PEDV remains unclear, especially in developing count… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

5
50
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
9
1

Relationship

4
6

Authors

Journals

citations
Cited by 50 publications
(55 citation statements)
references
References 95 publications
5
50
0
Order By: Relevance
“…The seasonality for the prevalence of PEDV has been gradually decreasing [ 37 , 38 ], and many provinces showed high incidence throughout the year, suggesting that the prevention and control of the epidemic should be strengthened in the summer and autumn when PEDV was low in the past. Furthermore, we found that Hunan and Hubei were the provinces with the most severe PEDV epidemics in south-central China, which is consistent with the study of He et al [ 39 ]. In addition, our results revealed that the GII-a subgroup has been increasing rapidly and has become dominant in recent years.…”
Section: Discussionsupporting
confidence: 92%
“…The seasonality for the prevalence of PEDV has been gradually decreasing [ 37 , 38 ], and many provinces showed high incidence throughout the year, suggesting that the prevention and control of the epidemic should be strengthened in the summer and autumn when PEDV was low in the past. Furthermore, we found that Hunan and Hubei were the provinces with the most severe PEDV epidemics in south-central China, which is consistent with the study of He et al [ 39 ]. In addition, our results revealed that the GII-a subgroup has been increasing rapidly and has become dominant in recent years.…”
Section: Discussionsupporting
confidence: 92%
“…Considering the dependence of the virus on host cell mechanisms, codon usage patterns can help us understand molecular evolution and expression levels and help vaccine design [17]. Recombination analysis of other pathogens with other DNA [18] and RNA [19] viruses, including recombination outages and evolutionary rates.…”
Section: Introductionmentioning
confidence: 99%
“…The texture of the food given is not appropriate, some babies still get a mashed texture when babies should be given soft food, so the process of eating is not successful, and the baby is not trained to chew properly (He, 2022). Following the theory of MP-ASI should be introduced at the age of 6 months because it is a critical period for infants to be introduced to solid foods gradually as stimulation of oromotor skills.…”
Section: Resultsmentioning
confidence: 99%